2018
DOI: 10.1101/439356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remapping in cerebral and cerebellar cortices is not restricted by somatotopy

Abstract: Cardinali for help in data collection, and Victoria Root for helpful comments on the manuscript. We thank Opcare for help with recruitment, and our participants for taking part in these studies.When a hand is missing, the brain region that typically processes information from that hand may instead process information from other body-parts, a phenomenon termed reorganization. It is commonly thought that only body-parts whose information is processed in regions adjacent to the hand region, could take up the reso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Since altered input is known to drive and shape brain organisation ( Recanzone et al., 1992 ; Wang et al., 1995 ), it is reasonable to expect that adapted behaviour substituting for the missing hand function can shape remapping. This is akin to recent studies in individuals with congenital hand loss, who exhibit remapping of multiple body parts, which are used for compensatory behaviours, including the feet, residual arm and lips ( Hahamy et al., 2017 ; Hahamy and Makin, 2019 ; Stoeckel et al., 2009 ) into the missing hand cortex. Considering that deprived cortex has been demonstrated to undergo network-level reorganisation in functional connectivity ( Makin et al., 2015a ), and that the connectome of the deprived cortex is wired to support hand function ( Glasser et al., 2016 ; Graziano and Aflalo, 2007 ), inputs relating to typical hand function (e.g.…”
Section: Additional Contributors To Remapping Beyond Deprivationmentioning
confidence: 84%
See 2 more Smart Citations
“…Since altered input is known to drive and shape brain organisation ( Recanzone et al., 1992 ; Wang et al., 1995 ), it is reasonable to expect that adapted behaviour substituting for the missing hand function can shape remapping. This is akin to recent studies in individuals with congenital hand loss, who exhibit remapping of multiple body parts, which are used for compensatory behaviours, including the feet, residual arm and lips ( Hahamy et al., 2017 ; Hahamy and Makin, 2019 ; Stoeckel et al., 2009 ) into the missing hand cortex. Considering that deprived cortex has been demonstrated to undergo network-level reorganisation in functional connectivity ( Makin et al., 2015a ), and that the connectome of the deprived cortex is wired to support hand function ( Glasser et al., 2016 ; Graziano and Aflalo, 2007 ), inputs relating to typical hand function (e.g.…”
Section: Additional Contributors To Remapping Beyond Deprivationmentioning
confidence: 84%
“…Thirdly, the traditional focus on S1 remapping due to changed selectivity to particular body parts is probably incomplete, considering net activity changes might not adequetly reveal the underlying functional processing. Moreover, related research in monkeys ( Kambi et al., 2014 ) and humans ( Hahamy et al., 2019 ) indicate that sensorimotor cortical remapping might reflect changes in sub-cortical terminals (e.g. brainstem, basal ganglia) or cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported lateral activity clusters in the cortical hand area, in addition to the medial foot area, in response to toe movement in individuals with bilateral congenital amelia (Stoeckel et al, 2009;Striem-Amit et al, 2018; see also Hahamy et al, 2017;Hahamy and Makin 2019) and passive toe stimulation in individuals with early childhood arm amputation (Yu et al, 2014(Yu et al, , 2006. Common to all such studies is the usage of univariate fMRI activity, where net changes in signal amplitude are averaged over a ROI.…”
Section: Foot Representation In the Hand Areamentioning
confidence: 99%
“…We studied toe activity patterns in the artists' SI foot area and sensorimotor (missing) hand area. Previous studies indicate that uni-or bilateral congenital hand absence leads to remapping of inputs from the mouth and feet into the deprived hand territory (Hahamy et al, 2017;Hahamy and Makin, 2019;Stoeckel et al, 2009;Striem-Amit et al, 2018;Yu et al, 2014Yu et al, , 2006. However, it is unclear whether such remapping truly represents recruitment of this zone to support toe function or aberrant activity, e.g., due to deprivation-driven inhibition reduction (Hahamy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%